find the product of (3q^9 + 3q^(7)) (-6q^-2 + 9)

1 answer

To find the product of the expressions \( (3q^9 + 3q^7) \) and \( (-6q^{-2} + 9) \), we can use the distributive property (also known as the FOIL method for binomials).

Let's multiply each term in the first expression by each term in the second expression:

  1. \( 3q^9 \cdot (-6q^{-2}) = -18q^{9 - 2} = -18q^7 \)
  2. \( 3q^9 \cdot 9 = 27q^9 \)
  3. \( 3q^7 \cdot (-6q^{-2}) = -18q^{7 - 2} = -18q^5 \)
  4. \( 3q^7 \cdot 9 = 27q^7 \)

Now, we combine all of these results together:

\[ -18q^7 + 27q^9 - 18q^5 + 27q^7 \]

Next, we'll combine the like terms:

  • Combine \( -18q^7 \) and \( 27q^7 \): \[ -18q^7 + 27q^7 = 9q^7 \]

Putting it all together, we get:

\[ 27q^9 + 9q^7 - 18q^5 \]

Thus, the final product of \( (3q^9 + 3q^7)(-6q^{-2} + 9) \) is:

\[ 27q^9 + 9q^7 - 18q^5 \]